Effects of a Small Interfering RNA Targeting YKL-40 Gene on the Proliferation and Invasion of Endometrial Cancer HEC-1A Cells. Issue 7 (1st September 2016) - Li, Li-li; Fan, Jiang-tao; Li, Da-hai; Liu, Yan
Abstract : Objective: The purpose of this study was to explore the effects of a small interfering RNA (siRNA) targeting YKL-40 on the proliferation and invasion of endometrial cancer (EC) HEC-1A cells. Methods: We used an siRNA targeting a sequence in YKL-40 (si- YKL-40 ) to transfect HEC-1A cells. Quantitative real-time polymerase chain reaction assay was performed to investigate the mRNA levels of YKL-40 . MTT, migration, and invasion assays were performed to identify the effects of si- YKL-40 on the proliferation, migration, and invasive abilities of the HEC-1A cells. Results: mRNA expression of YKL-40 was down-regulated in HEC-1A cells after transfection with si- YKL-40 ( P < 0.05). The proliferation, migration, and invasive abilities of HEC-1A cells were inhibited by siRNA ( P < 0.05). Conclusions: YKL-40 targeting siRNA specifically blocks the activity of YKL-40 in human EC HEC-1A cells, resulting in tumor suppression. This indicates that YKL-40 might serve as a potential small molecule target in the treatment of EC.